EFFICIENCY OF BIOLOGICAL CONTROL OF FALL ARMYWORM IN SWEET CORN - Costa Mortoni, Diogo Murillo (REVISTA DE AGRICULTURA, 2023)
The cultivation of sweet corn has great importance in Brazil due to its nutritional quality and several possibilities for use. It is a crop that attracts a large number of pests, especially the carcass caterpillar, which can generate great qualitative and quantitative losses. Because it is mainly used in natura the application of agrochemicals to the control of these pests can cause risk to human health. Thus, the experiment was carried out with the objective of testing the efficiency of the use of biological insecticides in comparison to conventional chemical insecticides in the control of the military caterpillar. The biological insecticides Bio BB, Bio MB, Bio Bt Premium Akb, Agree and Bac-Control WP and the chemical insecticides Dimax 480 SC and Incrível, were applied in the maize crop at 3 different times at 28, 43 and 50 days after seeding. In all applications, the biological products proved to be as efficient in controlling the caterpillar carcass as the chemical insecticides. The products based on Beauveria bassiana and Metharrizium anisopliae showed greater efficiency in pest control proving that the biological insecticides are efficient in pest control in sweet corn contributing to a sustainable management of the crop.